DIRECTIONS FOR THE REFORM OF UKRAINIAN CRIMINAL LEGISLATION IN THE FIELD OF TRANSPLANTATION OF HUMAN ANATOMICAL MATERIALS - Topchii, Vasyl; Zherzh, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to determine the main directions of reforming the criminal legislation of Ukraine in the field of transplantation of human anatomical materials based on the study of the positive experience of individual foreign countries (Belgium, Great Britain, Spain, Germany and the post-Soviet states). The methodological basis of the study was made up of general scientific methods of knowledge, with the help of which the author had the opportunity to outline ways to improve criminal liability for crimes related to illegal transplantation at the present stage. Results: the author emphasizes the need to make specific amendments to Articles 143, 149 and 115 of the Criminal Code of Ukraine in order to improve criminal legislation in the field of transplantology. Discussion: the author states that the number of recorded crimes in the field of transplantation of human anatomical materials over the past 10 years is insignificant, which may indicate the irrelevance of the chosen topic, but this is evidence of the problem of latency of the studied category of crimes and requires detailed study. General information on the number of recorded crimes provided for in art. 143, 149 of the Criminal Code of Ukraine, and the results of their pre-trial investigation for 2013-2020 indicate the artificial type of latency of these crimes when information about the illegal transplantation of human anatomical materials is received by law enforcement agencies, however, due to corruption links or lack of competence, etc., this information is not properly implemented in criminal procedure. The latency of this crime is also explained not only by the lack of experience in combating its identification, but also by the passivity of witnesses and victims as a result of distrust of the activities of law enforcement agencies, and the imperfection of criminal law. The article proposes amendments to the criminal legislation of Ukraine in the field of transplantology in order to eliminate the gaps in criminal legislation existing in practice. A promising study in this area remains the further study of the problems of illegal transplantation of human anatomical materials and the creation in the coming years of a number of secondary regulatory legal acts that will help to eliminate all existing gaps in criminal legislation and related to it in the field of transplantology.